Consumer Loyalty of Shopee’s User in South Sumatera through Experiential Marketing - Iisnawati Iisnawati; Nofiawaty Nofiawaty; Achmad Nazaruddin (Faculty of Economics, Universitas Sriwijaya, 2019)
The ease of getting information on the internet makes the consumers easy to move to other brands. Experiential Marketing is one of the alternative solutions that can be used by Shopee -as one of the players in the online trading industry in South Sumatera- toincrease their consumer loyalty. Through 5 aspects of experiential marketing namely Sense, Feel, Think, Act, and Relate. Shopee can build lasting relationships with their consumers. This study aims to determine the effect of Experiential Marketing on Consumer Loyalty of Shopee Users in South Sumatera. The population of this study is Shopee users in South Sumatera who have made transactions through Shopee more than once with a total sample of 120 samples. This research will use multiple linear regression analysis with SPSS. The results of the study showed that simultaneous experiential marketing had a significant effect on loyalty of Shopee consumer in South Sumatera. The results also showed, in partially that variable of Think did not significantly influence loyalty of Shopee consumer in South Sumatera.